ANALISIS PEMELIHARAAN MESIN CCO (CRUDE COCONUT OIL) STUDI KASUS PADA PT. SPO AGRO RESOURCES - Sartika, DEWI (Fakultas Ekonomi Universitas Tadulako, 2020)
This study aims to determine and analyze machine maintenance carried out by PT. SPO Agro Resources and to find out whether the presence of preventive maintenance policies can improve the effectiveness of time and costs. This research uses qualitative methods by describing maintenance activities carried out by PT. SPO Agro Resources, as well as using quantitative methods in the form of mathematical statistics as a tool to help decide policies to be taken at a certain time period and efficiency measurements using descriptive percentages. The results showed preventive maintenance costs once a month Rp.138,012,968, - efficiency value was 39.63%, preventive maintenance costs every two months Rp.196,689,315, - efficiency value was 56.48%, preventive maintenance costs every three months Rp. 258,731,341, - the efficiency value is 74.29%, repair maintenance costs Rp.247,164,000, - the efficiency value is 70.97%. Based on the calculation it is known that the policy that makes maintenance costs efficient is maintenance once a month because this policy is the smallest maintenance cost compared to other policies, where the percentage value is smaller which is 39.63%, according to table 2 which states if the calculation results are below 60% said to be very efficient.